Pollen morphology of Quercus sect. Ilex and its relevance for fossil pollen identification in southwest China. Issue 6 (2nd November 2018) - Zhang, Xiao; Huang, Kang-You; Zheng, Zhuo; Zhang, Ya-Ze; Wan, Qiu-Chi; Tian, Li-Ping
Abstract: Pollen grains of 16 modern species of Quercus were examined by scanning electron microscopy (SEM) and light microscopy (LM). The focus of this investigation was on a small group ( c . eight species) of alpine, sclerophyllous oaks that may form a monophyletic group within sect. Ilex . The data were combined with published data for Polar axis ( P ) and Equatorial diameter ( E ) for more than 80 species. Based on pollen morphology Quercus pollen grains were divided into three types: (1) The Cyclobalanopsis type is smallest (generally < 23 μm) in size, with P / E ratios of approximately 1.08 and a psilate or fine-grained surface; (2) Quercus sect. Ilex type is 23–29 μm, the P / E ratio is approximately 1.24 (prolate) and it has a rugulate pollen surface; (3) the Quercus sect. Quercus type is generally > 29 μm in size, has a P / E ratio of approximately 1.04, and a clearly verrucate pollen surface. Based on a comparison with modern pollen size and ornamentation, fossil pollen grains of the Quaternary Qinghai Lake core can be assigned to the Chinese southwest mountain oak group of Quercus sect. Ilex (in particular Quercus semecarpifolia ). In addition, we show that the pollen percentages of Quercus rapidly increased to the highest level during the glacial period. Using SEM for the identification of fossil Quercus pollen grains is essential to ensure the accuracy of differentiating evergreen Quercus types (sect. Ilex versus sect. Cyclobalanopsis ) during the last glacial period in southwest China.